Focusing on the spirit of ramadhan - Zuraina, Ali (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
8 August 2012. Ramadhan came again and CMLHS was eager to enliven the Holy month. One of the biggest activities was the Iftar Gotongroyong at UMP Mosque.